Tinjauan Yuridis terhadap Penerapan Restorative Justice dalam Penyelesaian Kasus Tindak Pidana Kekerasan dalam Rumah Tangga di Wilayah Hukum Polres Sabu Raijua - Claudio Rosonerri Miha Lena; Orpa Ganefo Manuain; Adrianus Djara Dima (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the juridical implementation of restorative justice in resolving domestic violence (KDRT) cases within the jurisdiction of the Sabu Raijua Police Resort, as well as to identify the supporting and inhibiting factors in its application. This research employs an empirical legal method with a sociological approach, using primary data obtained through interviews and observations, and secondary data from legal documents and literature. The findings indicate that the implementation of restorative justice has been carried out in accordance with Indonesian National Police Regulation Number 8 of 2021 and is applied selectively based on the type of offense, level of violence, and fulfillment of formal and material requirements. Empirical data from 2023 to 2025 show that out of 15 reported cases of domestic violence, 13 cases (86.7%) were successfully resolved through restorative justice, while 2 cases proceeded to formal legal processes due to the severity of the impact and the victim’s refusal to settle. The study also reveals that the effectiveness of restorative justice is supported by the active role of law enforcement officers, voluntary agreements between victims and perpetrators, and local cultural values emphasizing deliberation and harmony. However, its implementation faces challenges, including limited public understanding and difficulties in reaching agreements. Therefore, strengthening institutional capacity and enhancing public awareness are necessary to optimize the application of restorative justice in a fair, effective, and sustainable manner.